EVALUASI KINERJA KEUANGAN PERUSAHAAN MAKANAN BERBASIS ANALISIS RASIO KEUANGAN: SEBUAH STUDI KASUS - Alexander Joseph Ibnu Wibowo (Politeknik Negeri Batam, 2018)
This study aims to analyze trends in financial performance of a food company and test the validity of financial ratio instruments that have been used by financial practitioners and academics. For this reason, we designed an exploratory study through a single case study at a food company listed on the Indonesia Stock Exchange (IDX). We analyze the company's financial data using a variety of ratio analysis commonly used in financial disciplines, such as operational ratios, financial ratios, and stock performance. The analysis was deepened by describing the results of factor analysis to test the validity of financial ratio instruments. We find that the company's financial performance tends to fluctuate over time. When viewed from the sales side, the company's performance showed an increase since 2010. If we observe the profit margin, the company's financial performance tends to decrease. Operational ratio trends also show a decline from 2013 to 2015. Furthermore, the results of factor analysis indicate that the ratio of net income to overall assets is the strongest indicator to measure the company's financial ratios. In contrast to previous studies, this study found that the ratio of operating income to equity was not proven valid as a measure of financial ratios. In summary, this study succeeded in providing significant contributions and novelty for practical and theoretical interests through the validation of financial ratios that are widely used so far.